Penambahan Vitamin C Pada Pengencer Spermatozoa Babi Landrace Yang Disimpan Pada Suhu 15ºC (ADDITION OF VITAMIN C IN DILUENT OF LANDRACE SPERM STORED IN TEMPERATURE OF 15ºC) - Bebas, Wayan; Budiasa, Made Kota; Astutik, Ika Yuni (Buletin Veteriner Udayana, 2015)
The aims of this study were to determine the viability and motility of Landrace pig’sspermatozoa in the Beltsville Thawing Solution (BTS) diluent with addition vitamin C which werestored at a temperature of 15ºC. During the storage process, metabolic activity of spermatozoaproduce free radicals that can reduce the viability and motility of spermatozoa thus it needs theaddition of antioxidants. Vitamin C is an antioxidant that can be used to scavengethe free radicals.This study used vitamin C added into the BTS diluent with scavenge dose is 0.1 mg/ml, 0.2 mg/mland a dose of 0.3 mg/ml. The results showed that a dose of 0.1 mg/ml is the best dose to maintainthe viability and motility of Landrace pigs spermatozoa were storage at a temperature of 15ºC.
Keywords: sperm; pig; vitamin C; viability; motility